Hydroxyethyl Starch 6% 130/0.4 in a Balanced Electrolyte Solution and Renal Function After Nephrectomy. (October 2020) - Lee, Ho-Jin; Kwon, Yongsuk; Bae, Jinyoung; Yoo, Seokha; Yoon, Hee-Chul; Yoon, Soo-Hyuk; Kim, Jin-Tae; Bahk, Jae-Hyon; Kim, Won Ho
Abstract : BACKGROUND: Although previous studies have reported nephrotoxicity associated with hydroxyethyl starch (HES), the long-term effect of HES on renal function after nephrectomy has rarely been reported. We evaluated the association between intraoperative HES administration and short- and long-term renal function after nephrectomy. METHODS: We retrospectively reviewed 1106 patients who underwent partial or radical nephrectomy. The patients were divided into 2 groups: patients who received (HES group) or did not receive 6% HES 130/0.4 intraoperatively (non-HES group). The primary outcome was new-onset chronic kidney disease (CKD) stage 3a (estimated glomerular filtration rate [eGFR] <60 mL/min/1.73 m 2 ) or higher or all-cause mortality during 60 months after surgery. Propensity score matching was performed to address baseline differences between the 2 groups. Renal survival determined by stage 3a and stage 5 CKD (eGFR <15 mL/min/1.73 m 2 ) or all-cause mortality were compared up to 60 months before and after matching. We compared postoperative acute kidney injury (AKI) and CKD upstaging in the matched cohort as secondary outcomes. Ordinal logistic regression and Cox proportional hazards regression analyses using inverse probability of treatment weighting were performed for postoperative AKI and our primary outcome, respectively. A subgroup analysis of partial nephrectomy was performed. RESULTS: Thirty percent of patients received HES intraoperatively. Balanced solution and 0.9% normal saline was administered during surgery in both groups. Renal survival was not significantly different between groups after matching (log-rank test P = .377 for our primary outcome, and P = .981 for stage 5 or all-cause mortality, respectively). In the matched cohort (HES group: n = 280, non-HES group: n = 280), the incidence of AKI or CKD upstaging at 1 year was not significantly different (AKI: n = 94, 33.6% in HES group versus n = 90, 32.1% in non-HES group; CKD upstaging: n = 132, 47.1% in HES group versus n = 122, 43.6% in non-HES group; odds ratio [OR], 1.16; 95% confidence interval [CI], 0.83–1.61; P = .396). Intraoperative HES administration was not associated with postoperative renal outcomes (AKI: OR, 0.97; 95% CI, 0.81–1.16; P = .723; CKD stage 3a or higher or all-cause mortality: hazard ratio, 1.01; 95% CI, 0.89–1.14; P = .920). Subgroup analysis yielded similar results. CONCLUSIONS: Intraoperative 6% HES 130/0.4 administration was not significantly associated with short- and long-term renal function or renal survival up to 5 years in patients undergoing partial or radical nephrectomy. However, wide CI including large harm effect precludes firm conclusion and inadequate assessment of safety cannot be ruled out by our results.